Tinjauan Pustaka Faktor-Faktor yang Mempengaruhi Perilaku Merokok pada Remaja Berdasarkan Health Belief Model (HBM) - Laisyah Shava Zein Haryanto; Luqman Effendi (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
Smoking behavior among adolescents in Indonesia remains a serious public health challenge with increasing prevalence. Adolescence is a vulnerable period where psychological factors and the social environment significantly influence the decision to smoke. This study aims to review the factors influencing smoking behavior among adolescents based on the Health Belief Model (HBM) theoretical framework. This study is a literature review that analyzes various research findings related to the determinants of smoking behavior using HBM components. The analysis shows that all dimensions of HBM play a role in shaping smoking behavior. Self-efficacy and perceived susceptibility were found to be the strongest predictors. Although adolescents have a good perceived severity of the dangers of smoking, they are often hindered by high perceived barriers, such as peer pressure and psychological dependence. Consistent cues to action and perceived benefits are proven to encourage prevention and smoking cessation efforts. Adolescent smoking behavior is strongly influenced by individual beliefs in self-ability and health risks. Health interventions should focus on strengthening self-control and managing social influences to reduce the number of adolescent smokers.